Mapping of the Quantitative Trait Loci and Candidate Genes Associated With Iron Efficiency in Maize - Xu, Jianqin; Qin, Xiaoxin; Zhu, Huaqing; Chen, Fanjun; Fu, Xiuyi; Yu, Futong (Frontiers in Plant Science, 2022)
Iron (Fe) is a mineral micronutrient for plants, and Fe deficiency is a major abiotic stress in crop production because of its low solubility under aerobic and alkaline conditions. In this study, eighteen maize inbred lines were used to preliminarily illustrate physiological mechanism underlying Fe deficiency tolerance. Then bi-parental linkage analysis was performed to identify the quantitative trait loci (QTLs) and candidate genes associated with Fe deficiency tolerance using the RIL population derived from the most Fe-efficient (Ye478) and Fe-inefficient (Wu312) inbred lines. A total of 24 QTLs was identified under different Fe nutritional status in the Ye478×Wu312 RIL population, explaining 6.1 - 26.6% of phenotypic variation. And ten candidate genes were identified in the QTL co-localizations. Plants have evolved two distinct mechanisms to solubilize and transport Fe to acclimate to Fe deficiency, including reduction-based strategy (Strategy I) and chelation-based strategy (Strategy II), and maize uses Strategy II. However, not only strategy II genes which included ZmYS1, ZmYS3 and ZmTOM2 were identified by linkage mapping, but also several genes involved in the uptake and homeostasis of Fe of strategy I plants were identified, including ZmFIT, ZmPYE, ZmILR3, ZmBTS and ZmEIN2. Furthermore, strategy II gene ZmYS1 and strategy II gene ZmBTS were significantly upregulated in the Fe-deficient roots and shoots of maize inbred lines, and responded to Fe deficiency more in shoots than in roots. Under Fe deficiency, greater upregulations of ZmYS1 and ZmBTS were observed in Fe-efficient parent Ye478, indicating that these genes may be associated with genotypic difference of Fe efficiency. Beyond that, ZmEIN2 and ZmILR3 which may be involved in strategy I Fe acquisition were found to be Fe deficiency-inducible in the shoots. This study demonstrates the use of natural variation to identify important Fe-deficiency-regulated genes, and provides further insights for understanding the response to Fe-deficiency stress in maize.